Small-sided games do not replicate all external and internal loads of a football match-play during pre-season: A case study - de Sousa Pinheiro, G.; Chiari Quintão, R.; Bertoli Nascimento, V.; Claudino, J. G.; Alves, A. L.; Teoldo da Costa, I.; Teoldo da Costa, V. (International Journal of Sports Science & Coaching, 2023)
This study investigated the differences in external and internal load during pre-season training sessions carried out with different SSGs and a friendly match in top-class professional football players. The study was conducted over a full pre-season. Participants were 9 male top-class professional football players (25 ± 5 years; 74 ± 8 kg; 177 ± 8 cm). The following variables were measured: training session duration (min), average heart rate (bpm), total distance (m), distance covered per minute (m/min), the total number of accelerations > 2.5 m/s2, number of accelerations > 2.5 m/s2 per minute, average distance of accelerations (m), the average value of acceleration (m/s2). One-way ANOVA was performed to analyze the variance of all evaluated variables. No differences were found in the average accelerations (m/s2) (0.128) among all the training formats. Moderate differences were found in number of accelerations > 2.5 m/s2 per minute (n2 = 0.396, moderate effect) and average distance of accelerations (n2 = 0.545). Strong differences were found in HR (n2 = 0.788, large effect), total distance (n2 = 0.797, strong effect), distance per minute (n2 = 0.775 strong effect), total number of accelerations > 2.5 m/s2 (n2 = 0.699 strong effect). Significant correlations were found just for the number of accelerations > 2.5 m/s2 and the number of accelerations > 2.5 m/s2 per minute with the 4v4, 8v8 and the FM (r = 0.828-0.890, r2 = 69% - 79%; p < 0.01). External and internal loads differ across different SSGs and a FM during the pre-season training sessions.